ANALYSIS OF THE NEEDS OF GENERAL PRACTITIONERS IN PUBLIC HEALTH CENTERS USING HEALTH WORKLOAD METHOD - Akbar, Muhammad Ikhsan; Ahmad, La Ode Ali Imran (Public Health of Indonesia, 2020)
Background: The availability of general practitioners in the public health center is still an important spotlight regarding the uneven distribution.Objective: The purpose of this study is to find out the total needs of general practitioners at public health centers, specifically at the Public Health Center of Tampo and Wapunto in Muna District.Methods: This study used a descriptive approach using health workload method analysis. Observation sheets were used for collecting data. Workload burden analysis was used by establishing health facilities and types of health human resources, setting available work time, setting workload components and time norms, calculating workload standards, supporting task standards and supporting task factors, and also calculating the needs of general practitioners.Results: The Public Health Center of Tampo lacked two general practitioners, and the Public Health Center of Wapunto lacked one general practitioner.Conclusion: The Public Health Centers of Tampo and Wapunto in Muna district need additional general practitioners in the efforts of providing optimal service particularly in preventive, promotive, curative and rehabilitative to the community.